1980
DOI: 10.1104/pp.65.1.126
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of δ-Aminolevulinic Acid from Glutamate in Agmenellum quadruplicatum

Abstract: 5-Aminolevulinic acid accumulated in the culture medium when Agmeneflum quadplicatum strain PR-6 was incubated in the presence of levulinic acid, a competitive inhibitor of 8-aminolevulinic acid dehydratase, and specifically labeled glutamate and glycine. The 8-aminolevulinic acid was purified using Dowex 50W-X8 and cleaved by periodate to yield succinic acid and formaldehyde. The distribution of radioactivity in the two fragments suggested that in blue-green algae the carbon skeleton of 8-aminolevulinic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Although not yet completely characterized, this 5-carbon path to ALA has been shown to operate in greening tissues of higher plants (5)(6)(7) and in greening algae, including members of the Cyanophycae (8)(9)(10), Rhodophycae (11) and Chlorophycae (8,12,13), and Euglena (14).…”
Section: 3137] (2 3)mentioning
confidence: 99%
“…Although not yet completely characterized, this 5-carbon path to ALA has been shown to operate in greening tissues of higher plants (5)(6)(7) and in greening algae, including members of the Cyanophycae (8)(9)(10), Rhodophycae (11) and Chlorophycae (8,12,13), and Euglena (14).…”
Section: 3137] (2 3)mentioning
confidence: 99%
“…This ALA is then used in the synthesis of hemes, vitamin B12, and bacteriochlorophyll. In the chloroplasts of higher plants (2), archaebacteria (9,10), certain eubacteria (16,33,34), cyanobacteria (1,7,24,30), algae (19,20,50,51), and phytoflagellates (29,49), ALA is formed in the C-5 pathway from the five-carbon skeleton of glutamate. Eight molecules of glutamate-derived ALA provide all of the carbon and nitrogen atoms for the formation of the porphyrin nucleus of one molecule of chlorophyll.…”
mentioning
confidence: 99%
“…We were surprised that GAB induced an excretion of ALA. Pigment synthesis in cyanobacteria is thought to be similar to that observed in higher plants. For example, Kipe-Nolt et al (17) demonstrated biosynthesis of ALA in cyanobacteria by monitoring ALA excretion in the presence of LA and suggested that glutamate is the major substrate for ALA synthesis (18). Isotope distribution studies using .…”
Section: Methodsmentioning
confidence: 99%
“…One of these, LA2, is a competitive inhibitor of ALA dehydratase (17,18), and effectively blocks protoporphyrin biosynthesis in both normal and iron-deficient cyanobacteria (1 1). The mechanism by which the second inhibitor, GAB, affects cyanobacteria is virtually unknown (12).…”
Section: Introductionmentioning
confidence: 99%